Solidarity economy - Quispe Andía, Raquel Giulianna (2020)
Solidarity economy, or social economy, is a proposal being pushed by European economists and philosophers that has found great echo in Latin America. ¿Is it possible to integrate the solidarity component into the economy? This question has proven fundamental to the different authors who, in light of the crisis of the current economic system, seek to find a more equitable alternative economy that puts value on men’s work. This article presents a review of the concept of solidarity economy, and the main ideas proposed by authors who aspire to build and alternative from different approaches. In order to compare the approaches to this concept, practical examples of its application and results in Peru will be mentioned.